KTE-X19 for relapsed or refractory adult B-cell acute lymphoblastic leukaemia: phase 2 results of the single-arm, open-label, multicentre ZUMA-3 study. Issue 10299 (7th August 2021) - Shah, Bijal D; Ghobadi, Armin; Oluwole, Olalekan O; Logan, Aaron C; Boissel, Nicolas; Cassaday, Ryan D; Leguay, Thibaut; Bishop, Michael R; Topp, Max S; Tzachanis, Dimitrios; O'Dwyer, Kristen M; Arellano, Martha L; et al.
Summary: Background: Despite treatment with novel therapies and allogeneic stem-cell transplant (allo-SCT) consolidation, outcomes in adult patients with relapsed or refractory B-precursor acute lymphoblastic leukaemia remain poor, underlining the need for more effective therapies. Methods: We report the pivotal phase 2 results of ZUMA-3, an international, multicentre, single-arm, open-label study evaluating the efficacy and safety of the autologous anti-CD19 chimeric antigen receptor (CAR) T-cell therapy KTE-X19 in adult patients with relapsed or refractory B-precursor acute lymphoblastic leukaemia. Patients were enrolled at 25 sites in the USA, Canada, and Europe. Eligible patients were aged 18 years or older, with Eastern Cooperative Oncology Group performance status of 0–1, and morphological disease in the bone marrow (>5% blasts). After leukapheresis and conditioning chemotherapy, patients received a single KTE-X19 infusion (1 × 10 6 CAR T cells per kg bodyweight). The primary endpoint was the rate of overall complete remission or complete remission with incomplete haematological recovery by central assessment. Duration of remission and relapse-free survival, overall survival, minimal residual disease (MRD) negativity rate, and allo-SCT rate were assessed as secondary endpoints. Efficacy and safety analyses were done in the treated population (all patients who received a dose of KTE-X19). This study is registered with ClinicalTrials.gov, NCT02614066 . Findings: Between Oct 1, 2018, and Oct 9, 2019, 71 patients were enrolled and underwent leukapheresis. KTE-X19 was successfully manufactured for 65 (92%) patients and administered to 55 (77%). The median age of treated patients was 40 years (IQR 28–52). At the median follow-up of 16·4 months (13·8–19·6), 39 patients (71%; 95% CI 57–82, p<0·0001) had complete remission or complete remission with incomplete haematological recovery, with 31 (56%) patients reaching complete remission. Median duration of remission was 12·8 months (95% CI 8·7–not estimable), median relapse-free survival was 11·6 months (2·7–15·5), and median overall survival was 18·2 months (15·9–not estimable). Among responders, the median overall survival was not reached, and 38 (97%) patients had MRD negativity. Ten (18%) patients received allo-SCT consolidation after KTE-X19 infusion. The most common adverse events of grade 3 or higher were anaemia (27 [49%] patients) and pyrexia (20 [36%] patients). 14 (25%) patients had infections of grade 3 or higher. Two grade 5 KTE-X19-related events occurred (brain herniation and septic shock). Cytokine release syndrome of grade 3 or higher occurred in 13 (24%) patients and neurological events of grade 3 or higher occurred in 14 (25%) patients. Interpretation: KTE-X19 showed a high rate of complete remission or complete remission with incomplete haematological recovery in adult patients with relapsed or refractory B-precursor acute lymphoblastic leukaemia, with the median overall survival not reached in responding patients, and a manageable safety profile. These findings indicate that KTE-X19 has the potential to confer long-term clinical benefit to these patients. Funding: Kite, a Gilead Company.